Exploring Talent Among The Adolescents of Punjab - Mohinder Singh (MO.RI Publishing, 2022)
Talent is the world’s most valuable resource. It is ability or skills that someone is born with. Talent is somewhat strange status in our society. The main objective of this paper was to explore talent among the adolescents of Jassipauwali village of Punjab. The data were taken from 80 adolescents. Among the 80 adolescents 48 male and 32 females were taken on random basis. Self-made questionnaire was used by the investigator for the purpose of collecting data from the adolescents. Item wise analysis was used to explore talent among the Adolescents. The result reveled that the he majority of the adolescents (81.25%) were singer, (72.5%) have dancing talent, 73.75% adolescents were Punjabi dancer, 67.5% adolescents perform dancing as a supporting role and 3.75% adolescents perform dancing at the international level. 65% adolescents win the trophy in the dancing competition at the village level and 1.25% at international level. (32.5%) read books during their leisure time and 28.75% watch T. V. Most of the adolescents reads religious and short stories books in their spare time.